Health of farmersaved maize seed in northeast Nigeria - Biemond, P.C.; Oguntade, O.; Stomph, T.; Kumar, P. Lava; Termorshuizen, A.J.; Struik, Paul C. (Springer, 2013)
Many Nigerian farmers depend for their seed on seed-producing farmers, the so-called informal Seed System (SS), but seed quality of the SS is unknown. Farmers planting low quality seed risk poor field emergence and low plant vigour as a result of low physiological quality or infection with seed-borne pathogens. The objective of this research was to test seed quality of maize seed from the informal SS in north-east Nigeria. A total of 46,500 seeds (93 samples of 500 seeds each) were tested for germination, off-types and seed health. Seed pathology was quantified by plating disinfected seeds onto agar, and identifying the fungi present after 3 days incubation. Twelve seed-borne pathogens were identified including Bipolaris maydis (found in 45 % of the farmer-produced samples), Botryodiplodia theobromae (97 %) and Curvularia lunata (38 %). All samples were infected with Fusarium verticillioides, with a median infection incidence of 59 % (2009) and 51 % (2010). None of the 93 samples tested passed the demands for certified seed of the National Agricultural Seeds Council (NASC) in Nigeria, in particular the maximum limit of five off-types per kg seed sample. Based on these results, seed-producing farmers must improve the health of seed. The NASC should revise the standards for off-type seeds to minimize the time spent by farmers sorting planting material.